The interdependence of mid-trimester blood pressure and glucose levels in shaping fetal growth and neonatal outcomes: implications for risk–benefit assessment and co-management - Lv, Lijuan; Yang, Jingbo; Li, Linjie; Huang, Chuanyi; Shi, Huihua; Fang, Yiwen; Zuo, Lushu; Liu, Ting; Duan, Hongli; Wen, Jiying; Yang, Qing; Henry, Amanda; et al. (BMC medicine, 2025)
Maternal hypertension and hyperglycemia are closely related but have distinct impacts on fetal growth and are managed independently. How the interdependence of blood pressure (BP) and glucose levels quantitatively influences risk patterns for abnormal fetal growth and neonatal complications remains unexplored. Maternal BP and fasting plasma glucose (FPG) levels were measured between 20 and 28 weeks of gestation in a cohort including 56,881 singleton pregnancies. Linear and quantile regression analyses were used to evaluate the relationship between BP and FPG. We examined the dose-response relationships between BP and FPG with small-for-gestational age (SGA) and large-for-gestational age (LGA) by using restricted cubic spline (RCS) curves. Additionally, multivariable fractional polynomial interaction (MFPI) analysis was conducted to assess the effects of higher versus lower BP levels across the full range of FPG levels. Heatmaps were created to visualize the contributions of BP and FPG by categorizing them into ordered groups. Quantile regression revealed consistent positive correlations between mean arterial pressure (MAP) and FPG, with a steeper increase in MAP coefficients above the 0.5 quantile of FPG. MAP had a non-linear positive association with SGA risk, while FPG showed a non-linear negative association. Heatmaps revealed the highest SGA risk with high BP (MAP ≥ 85 mmHg)/low glucose (< 85 mg/dL) combinations and the lowest risk with low BP (MAP < 85 mmHg)/high glucose (≥ 85 mg/dL), with equivalent risk at both high BP/high glucose and low BP/low glucose. In hypertensive patients, SGA risk worsened continuously as glucose levels decreased. LGA risk was not influenced by BP levels. Neonatal complications decreased by approximately 47% as MAP declined from the highest to lowest category, and by about 17% with decreasing glucose levels. Based on a large pregnancy cohort in China, this study revealed an interdependent association between maternal BP and glucose levels and their combined impact on the risk of SGA. It provided quantitative evidence of how this interdependence shapes the transition of risk patterns for SGA, neonatal complications, and LGA. These findings underscore the need for an integrated approach to co-managing BP and glucose levels during pregnancy.